The Clark Air Base Nursery School a case study - Almeda, Alice L. ([Quezon City s.n.], 1973)
The Base Nursery School serves the dependents of American military and civilian personnel residing at Clark Air Base. It offers (1) a composite model program approach to provide more individualized curricula fitting the background and experience of the pupils at CAB, and (2) health, safety, nutrition and private transportation services to pupils.
Thesis (M. Ed.)--University of the Philippines.
Keywords: Clark Air Base Nursery School; Nursery schools -- Philippines